Impact of Narrow vs. Broad-Spectrum Surgical Antibiotic Prophylaxis in Pediatric Patients with Enteral Tubes Undergoing Cardiac Surgery. (4th October 2017) - Flett, Kelly B; Carpenter, Jane; Potter-Bynoe, Gail; Morrow, Deborah; Murji, Shaila; Sandora, Thomas J
Abstract: Background: Narrow-spectrum antibiotic prophylaxis is recommended for prevention of surgical site infection (SSI) in cardiac surgery. Enteral tubes in children are often near the incision and could affect the microbiology of SSI. We evaluated SSI rates before and after a 2014 practice shift at our institution, in which prophylaxis for patients with enteral tubes undergoing cardiac surgery changed from cefazolin to piperacillin-tazobactam. Methods: Retrospective cohort study of pediatric cardiac surgery cases performed at a tertiary children's hospital from 2009 to 2015. Data were obtained from the institutional data warehouse and from active SSI surveillance. Cases were excluded if the cardiac procedure was not the primary procedure or if data on perioperative antibiotics were not available. Rates of SSI per 100 procedures were calculated for all patients and for the subset with enteral tubes (gastrostomy, jejunostomy, colostomy). The most common SSI organisms were identified for each group. For patients with enteral tubes, we compared SSI rate among cases that received only cefazolin with cases that received piperacillin-tazobactam. Results: 6749 operations in 5490 patients were eligible for analysis during the study period. SSI rate was 1.7% ( n = 112) and varied from 1.0 to 2.3% annually. Among 438 operations (6.5%) during which the patient had an enteral tube, the SSI rate was 2.3% ( n = 10) and varied from 0–3.4% annually. S. aureus was the most common organism in all SSI (54%) and in those associated with enteral tubes (50%). Gram-negative bacteria were identified in 18% of all SSI and in 20% of those with enteral tubes. Cefazolin was used for 91% of all cardiac surgeries. Following the change in practice, cefazolin was used in 84% of surgeries; piperacillin-tazobactam was used in 12% of surgeries and in 93% of patients with enteral tubes. Among patients with enteral tubes, the SSI rate in cases receiving cefazolin ( n = 210) was 2.9% compared with 1.5% in those receiving piperacillin-tazobactam ( n = 201) ( P < 0.50). Conclusion: Among pediatric patients undergoing cardiac surgery, SSI rates in patients with enteral tubes are low and are not significantly reduced by broad-spectrum antibiotic prophylaxis. Disclosures: All authors: No reported disclosures.